Saprolegnia oliviae sp. nov. isolated from an Argentine river (Tierra del Fuego Province, Argentina) - Steciow, Mónica Mirta (2003)
Saprolegnia oliviae sp. nov. is described from litter (floating dead twigs, leaves and roots) in the Olivia River, Ushuaia Department, Tierra del Fuego Province (Argentina). The new species is illustrated and compared with other species of the genus. Distinguishing characteristics of S. oliviae are the production of smooth oogonia (with some lateral or terminal projections) and the absence of antheridial branches on the majority of the oogonia, but when present, they are mostly diclinous, at times oogonia are supplied with androgynous and monoclinous antheridial branches. The oogonial stalks are predominantly short and straight or long and bent, curved or many times coiled; oospores are distinctive subcentric, (1-) 15-50 (-70) per oogonium. Morphological details of the new species and its comparison with other described species are discussed here.